AB0582 Traditional cardiovascular risk factors in psoriatic arthropathy. association with cardiovascular events. (23rd January 2014) - Albert, G.; Ricse, M.; Aparicio, M.; Martin, I.; Nolla, J. M.; Rodríguez, J.
Abstract : Background: Inflammatory diseases seem to be associated with increased cardiovascular risk in relation to the disease itself. In patients with psoriatic arthritis (PsA) there is evidence of increased morbidity and mortality related to cardiovascular risk factors (CVRF), both in the classical: smoking, hypertension, dyslipidemia, diabetes mellitus (DM), and obesity ; and non-conventional: CRP, fibrinogen and homocysteine. Objectives: To determine the prevalence of classical cardiovascular risk factors in a series of PsA and determine its association with cardiovascular events. Methods: Cross-sectional study of an observational controlled per protocol cohort in a rheumatology department of a university hospital, the study includes an observation period of 20 years (1992-2012). All patients fulfilled the CASPAR criteria. We included 226 patients who had been visited in 2012. We analyzed the demographic variables of disease, the variables traditionally associated with cardiovascular risk (BMI, hypertension, dyslipidemia, DM, smoking, blood lipid levels) and cardiovascular events recorded (ischemic heart disease, cerebral vascular accidents, arterial peripheral ischemia). Statistics: descriptive usual, ANOVA, chi-square, Fisher test, SPSS v.15. Results: Of the 226 patients studied, 7.5% (17 patients) had had at least one cardiovascular event. We found a significant association (p <0.05) with increasing age, male sex, history of DM, dyslipidemia, hypertension and BMI> 25 (overweight and obesity), as well as higher levels of LDL cholesterol and triglycerides at the time the study. We found no association with active smoking, blood pressure, total cholesterol and HDL at the time of the study. Conclusions: In our series of PsA the presence of classical cardiovascular risk factors were significantly associated with the prevalence of cardiovascular events. Disclosure of Interest: None Declared